Advanced Strategies for Improving Lithium Storage Performance under Cryogenic Conditions. Issue 9 (15th January 2023) - Zheng, Yiwei; Qian, Tao; Zhou, Jinqiu; Liu, Jie; Wang, Zhenkang; Wang, Sai; Wang, Yiwen; Yan, Chenglin
Abstract: As a vital technology in portable electronic equipment, electric vehicle, and stationary energy storage, lithium‐based batteries are currently gaining widespread attention. However, when batteries are used more frequently, there are greater worries regarding their susceptibility to temperature, especially at low temperatures (LTs). In this review, the factors that lead to capacity loss in lithium‐based batteries at LT are analyzed and a summary of the most recent cutting‐edge approaches for improving LT kinetics is provided. In order to achieve satisfactory LT performance, electrode technology, interface chemistry, and electrolyte engineering must be taken into account during the cell design process. The recently revealed unique cryogenic storage mode and design concepts are also thoroughly introduced in this review, which is intended to motivate researchers in related domains. Finally, new insights, intriguing concepts, and workable solutions are proposed to promote the ongoing development of high‐performance cryogenic lithium batteries. Abstract : The problem of capacity fading at low temperatures (LTs) is receiving increasing attention as a result of the widespread use of lithium batteries. This review explores the factors that lead to lithium‐based batteries deteriorating at LTs and presents the most innovative solutions including electrode technology, interface chemistry, and electrolyte engineering.